Scope, Influence, and Interdisciplinary Collaboration: The Publication Portfolio of the NIH Clinical and Translational Science Awards (CTSA) Program From 2006 Through 2017. - Llewellyn, Nicole; Carter, Dorothy R.; DiazGranados, Deborah; Pelfrey, Clara; Rollins, Latrice; Nehl, Eric J. (Evaluation & the Health Professions, 2020)
The Clinical and Translational Science Awards (CTSA) program sponsors an array of innovative, collaborative research. This study uses complementary bibliometric approaches to assess the scope, influence, and interdisciplinary collaboration of publications supported by single CTSA hubs and those supported by multiple hubs. Authors identified articles acknowledging CTSA support and assessed the disciplinary scope of research areas represented in that publication portfolio, their citation influence, interdisciplinary overlap among research categories, and characteristics of publications supported by multihub collaborations. Since 2006, CTSA hubs supported 69,436 articles published in 4,927 journals and 189 research areas. The portfolio is well distributed across diverse research areas with above-average citation influence. Most supported publications involved clinical/health sciences, for example, neurology and pediatrics; life sciences, for example, neuroscience and immunology; or a combination of the two. Publications supported by multihub collaborations had distinct content emphasis, stronger citation influence, and greater interdisciplinary overlap. This study characterizes the CTSA consortium's contributions to clinical and translational science, identifies content areas of strength, and provides evidence for the success of multihub collaborations. These methods lay the foundation for future investigation of the best policies and priorities for fostering translational science and allow hubs to understand their progress benchmarked against the larger consortium.